1997
DOI: 10.1007/s004390050549
|View full text |Cite
|
Sign up to set email alerts
|

A candidate gene for hemochromatosis: frequency of the C282Y and H63D mutations

Abstract: The gene whose alteration causes hereditary hemochromatosis (HFE according to the international nomenclature) was, more than 20 years ago, shown to map to 6p21.3. It has since escaped all efforts to identify it by positional cloning strategies. Quite recently, a gene named HLA-H was reported as being responsible for the disease. Two missense mutations, Cys282Tyr (C282Y) and His63Asp (H63D), were observed, but no proof was produced that the gene described is the hemochromatosis gene. To validate this gene as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
48
1
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(55 citation statements)
references
References 11 publications
4
48
1
2
Order By: Relevance
“…These findings are different from those reported for Northern Europe, where more than 90% of the patients are C282Y homozygotes or C282Y and H63D compound heterozygotes (5,(20)(21)(22)(23)(24)(25), but agree with recent data reported for Italy, where approximately one third of the patients with HH showed neither C282Y or H63D mutations, nor any other mutation in the HFE gene by sequence analysis (26)(27)(28). Similarly, none of these mutations were detected in African Americans with HH or in subjects with African iron overload, another hereditary disorder of iron metabolism that is much more heterogeneous than HH (12,13).…”
Section: Discussioncontrasting
confidence: 86%
“…These findings are different from those reported for Northern Europe, where more than 90% of the patients are C282Y homozygotes or C282Y and H63D compound heterozygotes (5,(20)(21)(22)(23)(24)(25), but agree with recent data reported for Italy, where approximately one third of the patients with HH showed neither C282Y or H63D mutations, nor any other mutation in the HFE gene by sequence analysis (26)(27)(28). Similarly, none of these mutations were detected in African Americans with HH or in subjects with African iron overload, another hereditary disorder of iron metabolism that is much more heterogeneous than HH (12,13).…”
Section: Discussioncontrasting
confidence: 86%
“…1 Worldwide, 69% to 100% of patients with typical phenotypic hemochromatosis are C282Y homozygotes. [1][2][3][4][5][6] In referral centers, within pedigrees with iron overload, close to 100% of typical patients are C282Y homozygotes. 1,4 Genetic testing has thus replaced liver biopsy in the diagnosis of hemochromatosis in many C282Y homozygotes.…”
mentioning
confidence: 99%
“…Studies in well-defined pedigrees have demonstrated that 83% to 100% of typical hemochromatosis patients have a missense mutation in the HFE gene that results in a cysteine-to-tyrosine substitution at codon 282 (C282Y). [4][5][6] Hemosiderosis is a common finding in nonbiliary causes of cirrhosis. It has been postulated that at least part of the explanation for this phenomenon is heterozygosity for the C282Y mutation.…”
mentioning
confidence: 99%